(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Black tea (Camellia sinensis) supplement on renal disorders has poorly been explored. The present study was aimed to identified essential polyphenols present in black tea and it’s the role in gentamicin (GEN) induced nephrotoxicity in mice. The polyphenols present in 2.5% black tea infusion (BT) was determined by HPLC and antioxidant activity was assessed by DPPH radical scavenging. The renoprotective role of BT (125 mg/kg and 250 mg/kg orally for 7 days) was assessed in GEN (80 mg/kg, i.p, daily for 7 days) induced mice. BUN and creatinine was estimated in blood and lipid peroxides, glutathione, catalase and protein was determined in renal tissues. Ten polyphenols including catechin, caffeic acid, rutin, sinapic acid, ferulic acid, p-coumaric acid, myricetin, gallic acid, quercetin and kaempferol were identified and quantified in BT by HPLC. Moreover, it also exhibited powerful DPPH radical scavenging property (IC50 74.75µg/mg black tea). Finally, BT not only significantly and dose dependently (p<0.05) lowered BUN and creatinine in blood and reduced lipid peroxides in kidney, but also eventually enhanced the cellular antioxidants, glutathione and catalase in renal tissues. Therefore, black tea could be a good source of polyphenols that may protect kidneys from gentamicin induced oxidative stress.